1995
DOI: 10.1002/ejsp.2420250304
|View full text |Cite
|
Sign up to set email alerts
|

How good is good luck? The role of counterfactual thinking in the perception of lucky and unlucky events

Abstract: Spontaneous references to 'luck' (e.g. in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 30 publications
5
72
0
Order By: Relevance
“…We predicted and found that it is the person who nearly loses everything who feels relatively lucky (cf. Teigen, 1995Teigen, , 1996, and it is this person who subsequently gambles more. We noted earlier that the implications of near wins and losses at gambling previously have been approached mainly from the perspective of counterfactual thinking (e.g., Roese, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We predicted and found that it is the person who nearly loses everything who feels relatively lucky (cf. Teigen, 1995Teigen, , 1996, and it is this person who subsequently gambles more. We noted earlier that the implications of near wins and losses at gambling previously have been approached mainly from the perspective of counterfactual thinking (e.g., Roese, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Both of our gamblers could easily imagine an alternative outcome to the one that they actually experienced. One type of counterfactual thinking (upward) involves the mutation of events so that a better than observed outcome is imagined, and its opposite (downward) involves the mutation of events so that a worse than observed outcome is imagined (e.g., Markman, Gavanski, Sherman, & McMullen, 1993, 1995Roese, 1994;Sanna, 1996). Our near big winner likely wishes during the spin that he will land on Jackpot; that easily imagined, but unattained outcome, forms the basis for an upward counterfactual.…”
Section: Counterfactual Thinkingmentioning
confidence: 99%
“…For example, comparative negative emotions, such as regret, or disappointment, are increased by so-called "counterfactual thoughts"; thoughts about what might have been. However, comparative positive emotions are increased by counterfactual thougths too (Koo, Algoe, Wilson, & Gilbert, 2008;Teigen, 1995Teigen, , 1997Teigen & Jensen, 2011). For example, happiness with their relationship was amplified after people thought about how things would be different if their partner was absent than when they thought about the presence of their partner (Koo et al, 2008).…”
Section: Underlying Mechanismsmentioning
confidence: 94%
“…For example, people who survive a plane crash can describe themselves as lucky, because a salient counterfactual to them compares their state to the unlucky people in the plane who did not survive (Teigen, 1995(Teigen, , 1997.…”
Section: Counterfactual Thinkingmentioning
confidence: 99%